An exploration of the methods to determine the protein‐specific synthesis and breakdown rates in vivo in humans. Issue 17 (8th September 2019) - Holm, Lars; Dideriksen, Kasper; Nielsen, Rie H.; Doessing, Simon; Bechshoeft, Rasmus L.; Højfeldt, Grith; Moberg, Marcus; Blomstrand, Eva; Reitelseder, Søren; van Hall, Gerrit
Abstract: The present study explores the methods to determine human in vivo protein‐specific myofibrillar and collagenous connective tissue protein fractional synthesis and breakdown rates. We found that in human myofibrillar proteins, the protein‐bound tracer disappearance method to determine the protein fractional breakdown rate (FBR) (via 2 H2 O ingestion, endogenous labeling of 2 H‐alanine that is incorporated into proteins, and FBR quantified by its disappearance from these proteins) has a comparable intrasubject reproducibility (range: 0.09–53.5%) as the established direct‐essential amino acid, here L‐ring‐ 13 C6 ‐phenylalanine, incorporation method to determine the muscle protein fractional synthesis rate (FSR) (range: 2.8–56.2%). Further, the determination of the protein breakdown in a protein structure with complex post‐translational processing and maturation, exemplified by human tendon tissue, was not achieved in this experimentation, but more investigation is encouraged to reveal the possibility. Finally, we found that muscle protein FBR measured with an essential amino acid tracer prelabeling is inappropriate presumably because of significant and prolonged intracellular recycling, which also may become a significant limitation for determination of the myofibrillar FSR when repeated infusion trials are completed in the same participants. Abstract : Methods to determine human in vivo protein‐specific fractional synthesis and breakdown rates are presented, and methodological pros and cons considerations are discussed.